Aktualisasi Makna Kerjasama (Living Al-Qur'an-Hadist di Desa Koto Petai-Kerinci-Jambi) - Rasidin Rasidin; Nurfadliyati Nurfadliyati; Kusmana Kusmana (AL QUDS : Jurnal Studi Alquran dan Hadis, 2021)
Actualization of the Cooperation Meaning (Living Al-Qur'an-Hadith in Koto Petai Village-Kerinci-Jambi)The  purpose of this study is to examines how  the actualization of the meaning of cooperation in the Koto Petai community. Based on this research, some forms of cooperation in the Koto Petai community, such as: Bampok, recitation on Ramadan night, slaughtering cow on Eid al-Fitr, 'skuduopihak" parties at wedding, etc, are living al-Qur'an and sunnah which has become the custom and culture of the people. The research method is a qualitative study using analytical description method that is describing the data that has been obtained in accordance with the object of research. The object of this research is the local wisdom of the culture of community cooperation in Kerinci Jambi, which is limited to  Koto Petai, Danau Kerinci District, Kerinci Regency. The source of research is through observation, interviews with documentation